Unexpected Selectivity of UV Light Activated Metal-Oxide-Semiconductor Gas Sensors by Two Different Redox Processes. (25th February 2016) - Li, Wenting; Xu, Gu
Abstract : The conflict between the two existing models was resolved, to provide a clear explanation for the unexpected "selectivity" found in UV light activated metal-oxide-semiconductor (MOS) gas sensors during the detection of reducing agents. A new model based on the dynamic equilibrium of adsorbed oxygen concentration was constructed by two types of responses: (1 ) when the MOS surface is adsorbed with oxygen, the conductance of the sensor increases upon injection of reducing agents (RA) ( α -type) and (2 ) when the MOS surface is not covered by oxygen, the conductance decreases upon injection of RA ( β -type). The proposed model was verified by the experiments of ZnO based MOS gas sensors, to reveal the origin of the unexpected "selectivity" found by the optimum intensity, where the current drop, due to the reaction between RA and MOS, which increases with UV power and levels with the reciprocal background current, which decreases with the UV power.